OSTRACODS ACROSS THE PERMIAN-TRIASSIC BOUNDARY IN WESTERN TETHYS: THE BULLA PARASTRATOTYPE (SOUTHERN ALPS, ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 2008)
Investigation of the ostracod fauna of the parastratotype of the Permian-Triassic boundary at Bulla in the Southern Alps produced 62 species belonging to 31 genera. They are all discussed and figured. This paper presents results of the first description of ostracods from this important site. One genus, Bairdiacratia n. gen., and 13 species are new: Glyptopleurina pasinii n. sp., Knoxiella ventrospinosa n. sp., Knightina bullaensis n. sp., Bairdia ortiseiensis n. sp., B. cheni n. sp., B. (Rectobairdia) kershawi n. sp., Bairdiacratia qinglai n.gen. n. sp., B. tergilata n. gen. n. sp., Microcheilinella lata n. sp., Parabythocythere chongpani n. sp., Cavellina bellerophonella n. sp., C. alpina n. sp. and C. triassica n. sp. The palaeocecological analysis of each unit is produced. The unconformity-paraconformity U1 is clearly reflected in the ostracod assemblages and is marked by a drop in diversity and abundance of specimens. It was followed by a change in the ostracod faunal composition. The Bulla Member displays maximum ostracod diversity and abundance linked with the trangressive trend reported for this period. The unconformity-paraconformity U2, at the boundary between the Bellerophon and Werfen formations (Bulla and Lower Tesero members) is the main extinction level for ostracods. The Lower Tesero, Lower Mazzin and Upper Tesero members have very poor faunas. The lower part of the Upper Mazzin Mb. is characterized by an uneven burst of diversity before the great period of taxonomic paucity observed during the late Griesbachian all over the world.